Thyroidectomy in high body mass index patients: A single center experience. (April 2016) - Milone, Marco; Musella, Mario; Conzo, Giovanni; Campana, Gabriele; De Filippo, Delia; Coretti, Guido; Amato, Maurizio; Salvatore, Giuseppe; Amato, Bruno; Milone, Francesco
Abstract: Background: To identify the correlation between high body mass index (BMI ≥ 25) and the risk of postoperative complications of thyroidectomy. Methods: A comparative study between thyroidectomy performed in normal or overweigh-obese patients has been performed. Postoperative outcomes, including hypocalcemia, laryngeal nerve palsy, bleeding, operation time and hospital stay, were evaluated. Results: A total of 266 patients underwent total thyroidectomy were included. Of them, 104 patients had a BMI below 25 and 162 patients had a BMI ≥ 25. There was no statistically significant difference in the occurrence of early or permanent hypoparathyroidism, recurrent laryngeal nerve palsy, bleeding complications, or postoperative duration of hospital stay. There was, however, a higher operative time in patients with a BMI ≥ 25. Conclusion: Despite the longer operative time, thyroidectomy can be performed safely in patients with a BMI ≥ 25.